The Hermeneutic Circle in the Tradition of Islamic Tafsiri: Implications for Renewal - Ritonga, Zulkarnaen; Mardhatillah, Zuyyina; Dzymirrah, Ilma; Taufiq, Muhammad (Universitas Muhammadiyah Surabaya, 2025)
This article examines the concept of the hermeneutic circle and its application in Islamic exegetical tradition, as well as its implications for contemporary Islamic legal reform. The hermeneutic circle, developed within Western hermeneutical philosophy, resonates with classical Islamic exegetical methodology that recognizes the dialectical relationship between text (al-nash), context (al-waqi'), and interpreter (al-mufassir). This study employs library research methods with a qualitative approach, and data are comprehensively analyzed using a descriptive-analytical approach by revealing how classical scholars who accepted and rejected the application of hermeneutical principles in their ijtihad debated, then analyzing these differences of opinion based on primary and secondary data sources. The findings indicate that the debate concerning hermeneutics in Islamic exegesis reflects the rich and complex dynamics of contemporary Islamic thought. Progressive groups view hermeneutics as a valuable opportunity to revitalize and refresh Islamic understanding in the modern era, while understanding of the hermeneutic circle can serve as an bridge for formulating Islamic legal reform methodologies that are responsive to changing times without losing textual authenticity. Practical implications include the reformulation of usul al-fiqh, reconstruction of maqasid al-shariah, and development of contextualist approaches in contemporary Islamic legal determination.